2022
DOI: 10.29228/joh.55058
|View full text |Cite
|
Sign up to set email alerts
|

Tarihsel Süreç İçerisinde Kadın Futbolunda Cinsiyet Eşitsizliği

Abstract: TARİHSEL SÜREÇ İÇERİSİNDE KADIN FUTBOLUNDA CİNSİYET EŞİTSİZLİĞİ 1 Mehmet KOÇAK 2 & Dila Şeyda TAŞDEMİR 3 Öz Derleme türünde hazırlanan bu çalışmanın amacı futbolda cinsiyet eşitsizliği kavramının kadın futbolu açısından incelemesidir. Kadınlar diğer çoğu alanda olduğu gibi futbolda da var olmak için çok fazla çaba göstermektedirler. Kadın futbolu, erkek futboluna oranla ilgi çekici bulunmadığından hem tarihsel süreçte çok fazla yer edinememiş hem de günümüze kadar geçen süreçte erkek futbolunun bilinirlilik, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…This discrepancy might be attributed to various organizational factors. Previous research has indicated that women perceive higher levels of job stress compared to men due to factors such as feeling pressure, experiencing discrimination, and lacking control over the work environment (Tharenou and Conroy, 1994;Kocak & Tasdemir, 2022). Women often feel the need to prove themselves and excel in their roles, which can contribute to heightened stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be attributed to various organizational factors. Previous research has indicated that women perceive higher levels of job stress compared to men due to factors such as feeling pressure, experiencing discrimination, and lacking control over the work environment (Tharenou and Conroy, 1994;Kocak & Tasdemir, 2022). Women often feel the need to prove themselves and excel in their roles, which can contribute to heightened stress levels.…”
Section: Discussionmentioning
confidence: 99%